Anomalously weak Labrador Sea convection and Atlantic overturning during the past 150 years - Thornalley, David; Oppo, Delia; Ortega, Pablo; Robson, Jon; Brierley, Chris; Davies, Renee; Hall, Ian; Moffa-Sanchez, Paola; Rose, Neil; Spooner, Peter; Yashayaev, Igor; Keigwin, Lloyd (Nature, 2018)
Nature publication on AMOC strength last 1600 years